Casa de memória transxingu: patrimônio cultural digital como preservação de patrimônio cultural ameaçado - MARTINS, Alan David Bitencourt (Universidade Federal do Pará, 2025)
Launched in 2003 by UNESCO, the Charter for the Preservation of Digital Heritage highlighted the importance of data preservation, since then efforts have been made to establish attractive principles that justify investments by governments and institutions to preserve this type of heritage, formed above all from the process of adopting digital information and communication technologies. In order to contribute to the discussion and understanding of this type of heritage and to collaborate with the construction of those principles, this work researched the process of creating the Collection of the Casa de Memória Transxingu, in Altamira, Pará, an essentially digital collection created to preserve the culture from the process of inventorying the cultural assets of the medium-low Xingu region, a way of compensating for the profound changes that the installation of the Belo Monte Hydroelectric Power Plant brought to the region. We show how the laws for the preservation of cultural heritage and the preservation of the environment were constructed and linked over time in order to preserve culture by determining the inventory of cultural assets in the region and detail the stages of idealization, projection and execution of the processes. of construction of the House of Memory, the inventory and assembly of the Museum Space intended to promote and preserve the Collection, discussing at each moment important points regarding the use of this type of heritage as a way of preserving cultural heritage, demonstrating how digital heritage can preserve cultural heritage by becoming a digital cultural heritage.